2018
DOI: 10.3389/fcimb.2018.00021
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation in Klebsiella pneumoniae Bacteremia Strains Was Found to be Associated with CC23 and the Presence of wcaG

Abstract: Klebsiella pneumoniae bacteremia biofilm traits and distribution characteristics have not been clarified. This study aimed to determine the prevalence and characteristics of K. pneumoniae bacteremia biofilm formation (BF) and to explore the virulence factors associated with K. pneumoniae BF. A total of 250 K. pneumoniae bacteremia isolates were collected from patients in Shenzhen and Shanghai, China. Virulence genes in their genomes were detected by PCR. The isolates were subjected to multilocus sequence typin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 38 publications
5
76
1
1
Order By: Relevance
“…The hypermucoviscous phenotype of K. pneumoniae isolates was confirmed by string test. The bacterial strains were grown on an agar plate at 37 • C overnight and the formation of a mucoviscous string measuring >5 mm on a bacteriology inoculation loop was defined as a positive string test (Zheng et al, 2018a).…”
Section: String Testmentioning
confidence: 99%
“…The hypermucoviscous phenotype of K. pneumoniae isolates was confirmed by string test. The bacterial strains were grown on an agar plate at 37 • C overnight and the formation of a mucoviscous string measuring >5 mm on a bacteriology inoculation loop was defined as a positive string test (Zheng et al, 2018a).…”
Section: String Testmentioning
confidence: 99%
“…Andrade et al (2014) suggested that biofilm formation contributed to the advancement of ST11 MDR K. pneumoniae. However, Zheng et al (2018) recently showed that ST23 strains of K. pneumoniae produce significantly greater quantities of biofilm than ST11 strains. In addition, Diago-Navarro et al (2014) demonstrated that ST23 strains also generate much more biofilm than isolates from the global MDR group ST258 which is related to the STT11 clone.…”
Section: The Virulence Component In Mdr K Pneumoniaementioning
confidence: 99%
“…The bacterial capsule could potentially protect hvKP from the assault of the antimicrobial peptides such as cathelicidins, defensins and bile salts present in colonic mucus (Antoni et al, ; Campos et al, ). The capsule may also aid in the formation of K. pneumoniae biofilms, which are more resistant to factors such as to antibiotics and starvation (Wu et al, ; Zheng et al, ).…”
Section: Introductionmentioning
confidence: 99%